Mixed polytype/polymorph formation in InSe films grown by molecular beam epitaxy on GaAs(111)B - Maria Hilse; Justin Rodriguez; Jennifer Gray; Jinyuan Yao; Shaoqing Ding; Derrick Shao Heng Liu; Mo Li; Joshua Young; Ying Liu; Roman Engel-Herbert (npj 2D Materials and Applications)
Abstract We report the growth of InSe films on semi-insulating GaAs(111)B substrates by molecular beam epitaxy (MBE). Excellent nucleation behavior resulted in the growth of smooth, single-phase InSe films. The dominant polytype was the targeted γ-InSe. Transmission electron microscopy revealed the presence of three bulk polytypes β, γ, and ε-InSe arranged in nanosized domains, which can be interpreted as sequences of stacking faults and rotational twin boundaries of γ-InSe. Additionally, a centrosymmetric Se-In-In-Se layer polymorph with $$P\bar{3}m$$ P 3 ̅ m symmetry was identified as typically not present in bulk. Sizeable differences in their electronic properties were found, which resulted in sizeable electronic disorder arising from the nanoscale polytype arrangement that dominated the electronic transport properties. While MBE is a viable synthesis route towards stabilization of InSe polytypes not present in the bulk, an improved understanding to form the targeted polymorph is required to ultimately inscribe a layer sequence on demand utilizing bottom-up synthesis approaches.